208k views
5 votes
Simplify this expression-6(a+8)

User SWB
by
5.5k points

2 Answers

2 votes

Answer:

-6a + 48

Explanation:

-6(a+8) (distribute -6 into the parentheses)

= (-6)a + (-6)8

= -6a - 48

User Myrtho
by
6.4k points
3 votes

Answer:

-6a - 48

Explanation:

To simplify this expression, we must distribute the -6 to each term inside the parentheses.

We can do this by multiplying -6 by each term.

-6 * a = -6a

-6 * 8 = -48

Let's put them together.

-6a - 48

So, our answer is -6a - 48

User David Luque
by
6.8k points